Energized Oxygen Treatment in Drinking Water for Laying Hens: An Alternative Disinfectant - ŞahanYapicier , Özlem; Saatci, Mustafa (International Journal of Poultry Science, 2018)
Background and Objectives: The objective of this study was to examine the effects of adding energized oxygen to drinking water for laying hens and evaluate quantities of microorganisms in fecal samples. Materials and Methods: Oxygen generated gas was hosed into the drinking water tank of the laying commercial farm. Cloacal swabs and conveyor samples taken for fecal samples were collected in three runs for microbiological analysis as follows: The first was before the application of energized O2 gas as a control, the second was after one week and the last was two weeks later. Results: The total bacteria and E. coli count from control to successive samples in cloacal swabs and conveyor samples decreased. However, there were no effects on fungal count. Conclusion: Energized oxygen may be used as an effective disinfectant to reduce microbiological exposure and improve the health of laying hens.